Estudio y propuesta para un plan de mantenimiento de la flota vehicular del Gobierno Autónomo Descentralizado del Cantón Sozoranga - Guerrero Saavedra, Roberto Carlos (2019)
In the present investigation a preventive maintenance plan was designed for the vehicles of the Autonomous Decentralized Government of the Sozoranga Canton. The first step that took place was the lifting of the technical information of each of the vehicles, as well as the collection of user manuals and information search of the vehicles that did not have that information essential for the generation of the plan of maintenance. The maintenance plan was developed taking into account first the vehicles considered vital for the institution, which was defined under a relevant priority analysis of each of the scenarios. The main purpose of preparing documents or templates for maintenance management is the organization of information and maintenance activities carried out within the facilities. It was suggested that an evaluation of the preventive maintenance plan be made one year after its implementation, in order to discover flaws and take corrective measures; It was also proposed to carry out the relevant procedures to provide the necessary training to the drivers and operators of the vehicles and machinery owned by the institution. The main purpose of the project is to contribute with a planning and control of activities to ensure the proper functioning of the vehicles in each of the scenarios intervened, through the implementation and management required by each of them and consequently improve the development of the different activities and functions that the GAD of Sozoranga fulfills.